Improving Students’ Entry Profiles: Exploring English Ability Level, Affective Variables and Academic Performance in a Chilean TEFL Program. - López, María Ester; Ramos Gálvez, Camilo (Colombian Applied Linguistics Journal, 2022)
Having valuable information about newly enrolled university students in the form of entry profiles is key to address their academic needs as they advance through their educational trajectories. In Chile, this is acknowledged by the law 20.903, which mandates that all tertiary-level pedagogy programs implement a diagnostic assessment at the beginning of their programs. This, in order to even out students' academic level and establish supportive measures for those who obtain low results. Aiming to enrich the entry profile of a group of Chilean TEFL undergraduates, our study explores how factors such as English ability level, attendance to class and motivation influence their academic performance during their first semester of university studies. Through the analysis of quantitative sources of data, results suggest that class attendance and scores on an institutional English entry test give valuable information about students’ performance, but do not fully explain their academic success. Qualitative data from teacher interviews suggest that profiling students would also involve looking at factors such as motivation. Findings make us reflect on the need of detailed entry profiles and comprehensive diagnostic assessments that transcend the assessment of English skills and linguistic knowledge in order to assure better learning trajectories for university students.